Chest compression rates of 60/min versus 90/min during neonatal cardiopulmonary resuscitation: a randomized controlled animal trial - Bruckner, Marlies; O'Reilly, Megan; Lee, Tze-Fun; Cheung, Po-Yin; Schmölzer, Georg M. (Frontiers in Pediatrics, 2023)
Background To compare chest compression (CC) rates of 60/min with 90/min and their effect on the time to return of spontaneous circulation (ROSC), survival, hemodynamic, and respiratory parameters. We hypothesized that asphyxiated newborn piglets that received CC at 60/min vs. 90/min during cardiopulmonary resuscitation would have a shorter time to ROSC. Methods Newborn piglets (n = 7/group) were anesthetized, tracheotomized and intubated, instrumented and exposed to 45 min normocapnic hypoxia followed by asphyxia and cardiac arrest. Piglets were randomly allocated to a CC rate of 60/min or 90/min. CC was performed using an automated CC machine using CC superimposed with sustained inflation. Hemodynamic parameters, respiratory parameters, and applied compression force were continuously measured. Results The mean (IQR) time to ROSC was 97 (65–149) s and 136 (88–395) s for CC rates of 60/min and 90/min, respectively (p = 0.31). The number of piglets that achieved ROSC was 5 (71%) and 5 (71%) with 60/min and 90/min CC rates, respectively (p = 1.00). Hemodynamic parameters (i.e., diastolic and mean blood pressure, carotid blood flow, stroke volume, end-diastolic volume, left ventricular contractile function) and respiratory parameters (i.e., minute ventilation, peak inflation and peak expiration flow) were all similar with a CC rate of 60/min compared to 90/min. Conclusion Time to ROSC, hemodynamic, and respiratory parameters were not significantly different between CC rates of 60/min vs. 90/min. Different CC rates during neonatal resuscitation warrant further investigation.